Peran Kementrian Agama Dalam Pembangunan Pendidikan Di Kabupaten Mandailing Natal - Lahuddin Rambe; Kholis Martua; Nur Ardila Rambe; Riska Pratama Tanjung; Nur Jannah Agriani (Universitas 45 Surabaya, 2024)
Vertical agencies of the Ministry of Religion are agencies within the Ministry of Religion that carry out the duties and functions of the Ministry of Religion in the regions. The vertical agencies of the Ministry of Religion consist of regional offices of the provincial Ministry of Religion and district/city offices of the Ministry of Religion. Development in the education sector is directed at